Retroperitoneal Giant Immature Teratoma Diagnosed at Birth and treated post-neonatally: A Case Report - Takezoe, Toshiko; Sumiya, Wakako; Mitani, Yuichi; Ichimura, Kayoko; Tsuzaka, Shoichi; Tsutsuno, Takashi; Ogawa, Shoko; Kondo, Yasuhiro; Deie, Kyoichi; Kawashima, Hiroshi (Journal of Neonatal Surgery, 2025)
Background: Immature retroperitoneal teratomas (RTs) are rare tumors predominantly diagnosed within the first year of life, with the majority being benign. Complete surgical resection is the primary treatment; however, surgical challenges due to anatomical complexities and perioperative complications often arise, particularly in neonates. This study presents a case of a congenital immature RT identified at birth, where the timing of surgical intervention was critically evaluated through a review of relevant literature. Case presentation: The patient, a male neonate born at 36 weeks, exhibited abdominal distention and was transferred for further evaluation. Imaging revealed a large retroperitoneal mass, leading to a diagnosis of immature teratoma. An initial biopsy confirmed the absence of malignancy, and surgical resection was delayed to allow for further development of the infant. The tumor, weighing 930 g, was successfully removed while preserving the right kidney, though postoperative urinary peritonitis occurred. The patient recovered and he was discharged with no recurrence after seven months. Conclusion: This case highlights the importance of carefully timing surgery in neonatal patients with complex conditions to minimize surgical risks.